Designing, Manufacturing, and Testing of 50 Wp Solar Panel Monitor Equipment Using Arduino and Internet of Things - Diyan Prayudi Susman; Cholilullah Rangkuti; Sentot Novianto (Penerbitan Universitas Trisakti, 2023)
Monitoring the performance of solar panels is very necessary to assess the performance of a solar panel in real environmental conditions. The aim of the research is to study the real-time monitoring of solar panel with an Internet of Things (IoT) System. The designed solar panel performance monitoring system is equipped with a wifi module, and voltage, temperature, and humidity sensors. The design of this solar panel monitoring system uses Arduino and the IoT system a function of by reading, sending, and processing data obtained by sensors. The performance monitoring system on this solar panel utilizes the concept of sending solar panel data to other components via the Internet. By using the internet which is integrated into applications and databases as data storage. The solar panels used in the test are Polycrystalline type with a capacity of 50 Wp. The result is that this tool has successfully tested four solar panels with accurate results under optimal condition.